Interface-enhanced emulsified asphalt composite magnesium phosphate cement repairing material and application thereof

By adding optimizer, interface enhancer and chemically modified fibers to the emulsified asphalt composite magnesium phosphate cement repair material, the problem of hydration and demulsification coordination during the composite of magnesium phosphate cement and emulsified asphalt is solved, and the mechanical properties and bonding ability of the repair material are improved, and better repair results are achieved.

CN119569413AActive Publication Date: 2025-03-07SHANDONG UNIV

Patent Information

Application Number
CN202510132968.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-07
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

When magnesium phosphate cement and emulsified asphalt are directly combined, there are problems that hydration and demulsification are difficult to coordinate, resulting in deterioration of the strength of the composite material and the problem of weak interface between the composite material and the repair interface.

Method used

Interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material is used to coordinate the hydration reaction of magnesium phosphate cement and the emulsified asphalt demulsification process by adding components such as optimizing agents, interface reinforcers and chemically modified fibers to enhance the bonding ability of the repair material and the repair interface.

Benefits of technology

The interaction between emulsified asphalt and magnesium phosphate cement is effectively coordinated, the mechanical properties and bonding ability of the repair materials are improved, the problem of weak interface areas is solved, and better repair results are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569413A_ABST
    Figure CN119569413A_ABST
Patent Text Reader

Abstract

The invention relates to the field of magnesium phosphate cement-based materials, and particularly discloses an interface-enhanced emulsified asphalt composite magnesium phosphate cement repairing material and application thereof. The repairing material comprises the following components in parts by weight: 400-600 parts of a magnesium phosphate cement-based material, 50-150 parts of emulsified asphalt, 5-10 parts of a toughening organic component, 10-15 parts of an optimizing agent, 8-20 parts of an interface reinforcing agent, 4-10 parts of chemically modified fibers and 80-100 parts of mixing water. The magnesium phosphate cement-based material comprises the following components in parts by weight: 150-300 parts of magnesium oxide powder, 70-150 parts of phosphate and 10-30 parts of a retarder. According to the invention, demulsification of the emulsified asphalt and hydration of the magnesium phosphate cement can be coordinated and matched with each other, the bonding capacity between the repairing material and a repairing interface can be enhanced, and the mechanical property of the repairing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnesium phosphate cement-based materials, and in particular to an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material and an application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Asphalt pavement has become the first choice for high-grade highways due to its good vibration and noise reduction performance and smooth and comfortable driving performance. However, due to the rapid increase in heavy traffic and the high sensitivity of asphalt to temperature, various road cracks and other diseases frequently occur, threatening driving safety. How to repair damaged pavement quickly and timely to extend the service life of the road is a difficult problem faced by road maintenance work. Traditional hot-mix asphalt repair consumes a lot of energy, is seriously affected by climate and is difficult to construct, while cold-mix asphalt repair has shortcomings such as being restricted by repair materials, slow strength formation and poor water stability.

[0004] Adding cement to emulsified asphalt mixture can improve its high temperature stability and water stability. The cement hydration process requires a large amount of water, which can accelerate the demulsification of emulsified asphalt, thereby improving the adhesion between asphalt and aggregate. Among them, cement plays a good regulating role in the mixture. It can hydrate to form cement stone inside the mixture to strengthen the internal structure, and it can also consume internal water through hydration reaction to further improve the strength. This cement-emulsified asphalt mixture fills the gap in the field of cold patch materials and is widely used. However, its strength development is still slow and its early strength is low, which makes it difficult to meet the needs of rapid repair.

[0005] Magnesium phosphate cement (MPC) is a new type of cementitious material. The basic principle of its coagulation and hardening is that phosphate ions react rapidly with dead-burned magnesium oxide in an acidic environment to form dense crystals. It has the advantages of rapid hardening and early strength, excellent bonding performance, good durability and excellent weather resistance. However, the present invention finds that when MPC and emulsified asphalt are directly compounded, there is a problem that the hydration of MPC and the demulsification of emulsified asphalt are difficult to coordinate, resulting in the deterioration of the strength of the composite material, and there is a problem of a weak interface area between the composite material and the repair interface. Summary of the invention

[0006] In view of the above problems, the present invention provides an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material and its application, which can not only coordinate the demulsification of emulsified asphalt and the hydration of magnesium phosphate cement, but also enhance the bonding ability between the repair material and the repair interface, and improve the mechanical properties of the repair material. Specifically, the technical solution of the present invention is as follows.

[0007] First, the present invention provides an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material, comprising the following components in parts by weight: 400-600 parts of magnesium phosphate cement-based material, 50-150 parts of emulsified asphalt, 5-10 parts of toughening organic component, 10-15 parts of optimizer, 8-20 parts of interface enhancer, 4-10 parts of chemically modified fiber, and 80-100 parts of mixing water.

[0008] Further, the magnesium phosphate cement-based material comprises: 150-300 parts by weight of magnesium oxide powder, 70-150 parts by weight of phosphate, and 10-30 parts by weight of retarder. Optionally, the phosphate comprises at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, and ammonium dihydrogen phosphate. The retarder comprises at least one of borax, boric acid, triethanolamine, and the like.

[0009] Furthermore, the solid content of the emulsified asphalt is 50-60%.

[0010] Further, the toughening organic component includes at least one of: waste tire powder, polyethylene rubber powder, polyurethane rubber powder, styrene-butadiene-styrene rubber powder (SBS), polypropylene fiber powder, cellulose ether powder, ethylene-vinyl acetate copolymer rubber powder, etc. Optionally, the toughening organic component has a fineness of 200-400 meshes.

[0011] Further, the optimizer includes at least one of thiobenzenesulfonic acid, sulfoaniline diethylenetriamine, cyclohexylphenyl ester, 2-ethylhexyl terephthalate, diisooctyl phthalate, octaalkyl sulfobetaine, sodium p-toluenesulfonate, hexadecyl dimethyl benzyl ammonium chloride, etc. The optimizer can effectively overcome and improve the synergy of emulsified asphalt and magnesium phosphate cement.

[0012] Furthermore, the interface enhancer is formed by mixing epoxy resin, polyamide, phthalic anhydride, rubber powder, and N,N-dimethylaniline in a mass ratio of 8-15: 0.3-0.5: 0.1-0.3: 0.5-1: 0.1-0.2. Optionally, the polyamide includes any one of polyhexamethylene adipamide, polyterephthalamide, and polycaprolactam. The interface enhancer can effectively eliminate the interface transition zone and strengthen the bonding ability between the repair material and the repair interface.

[0013] Furthermore, the preparation method of the chemically modified fiber comprises: placing the basalt fiber in an alkali solution and allowing it to stand for surface treatment. After completion, the basalt fiber is separated, washed, and placed in a modifier for heating and heat preservation treatment. After completion, the fiber is washed and dried to obtain the chemically modified fiber. The modifier comprises at least one of trichlorofluorosilane, 3-aminopropyltriethoxysilane, aminophenylsilane, styrene, acrylic acid, etc.

[0014] Furthermore, the ratio of the basalt fiber to the alkali solution is 1g: 20-40ml. Optionally, the mass fraction of the alkali solution is 1-5%. The alkali solution includes any one of sodium hydroxide solution, potassium hydroxide solution, ammonia water, etc.

[0015] Furthermore, the length of the basalt fiber is 5-30 mm.

[0016] Furthermore, the standing time is 2 to 6 hours. The surface reactivity of the basalt fiber can be effectively improved by the alkali solution treatment so as to react with the active groups in the modifier.

[0017] Furthermore, the heating temperature is 50-80° C., and the heat preservation time is 2-6 hours. During this process, the basalt fiber can be completely immersed in the modifier.

[0018] Furthermore, the drying temperature is 60-80° C., and the drying time is 20-24 hours.

[0019] Furthermore, the repair material further includes an additive, such as 3-7 parts by weight of a water reducer and 1-4 parts by weight of a defoamer. Optionally, the water reducer includes at least one of a naphthalene-based water reducer, a polycarboxylic acid water reducer, a lignin water reducer, etc. The defoamer includes at least one of an organic silicon defoamer, a fatty acid defoamer, a polyether defoamer, etc.

[0020] Secondly, the present invention provides the application of the interface enhanced emulsified asphalt composite magnesium phosphate cement repair material in the fields of construction engineering, road engineering, bridge engineering, water conservancy and hydropower engineering, marine engineering, etc.

[0021] Compared with the prior art, the present invention has at least the following beneficial technical effects: The present invention not only compounds magnesium phosphate cement and emulsified asphalt, but also adds components such as optimizers, interface enhancers and chemically modified fibers, which not only breaks the compatibility barrier between organic and inorganic substances in emulsified asphalt and magnesium phosphate cement, promoting better fusion of the two, but also enhances the bonding ability between the repair material and the repair interface, thereby improving the mechanical properties of the repair material.

[0022] (1) The present invention utilizes the molecular characteristics of nitrobenzene sulfonic acid and thiobenzene sulfonic acid in the optimizer, which have nitro and sulfonic acid groups, to regulate the hydration reaction rate of magnesium phosphate cement, ensure a longer working time and increase the convenience of construction. At the same time, the sulfonic acid group has the effect of better dispersing the magnesium phosphate cement slurry and reducing the aggregation of particles in the liquid, thereby avoiding the formation of a large range of weak areas that damage the strength of the repair material. In addition, the thiobenzene sulfonic acid can also form a coordination compound with the magnesium ions in the magnesium phosphate cement, enhance the water resistance and corrosion resistance of the cement, and form an emulsified asphalt composite magnesium phosphate cement repair material with strong construction performance and good durability. The sulfoaniline diethylenetriamine, octaalkyl sulfobetaine, hexadecyl dimethyl benzyl ammonium chloride and sodium p-toluenesulfonate in the optimizer can assist the hydration products of magnesium phosphate cement and asphalt colloidal particles to be evenly distributed in the repair material system by reducing the surface tension of the solution, improve the fluidity and water resistance of the repair material, thereby facilitating the formation of an interlaced network structure between the hydration products and the emulsified asphalt, improving the strength and weather resistance of the repair material, and enabling it to have the ability to be constructed in multiple scenarios. The cyclohexylphenyl ester in the optimizer can not only improve the fluidity and workability of the repair material of the present invention, but also the benzene ring part and cyclohexyl part of the cyclohexylphenyl ester can interact with the surface of cement particles, and improve the wettability of cement by combining with the cement surface molecules. This effect helps to evenly disperse the cement particles, reduce the aggregation and agglomeration between particles, and improve the uniformity of the repair material. The diisooctyl phthalate and 2-ethylhexyl terephthalate can effectively improve the toughness of the repair material of the present invention, and improve the crack resistance of the asphalt itself (especially in low temperature environment), reduce cracks caused by low temperature, and delay the aging rate of emulsified asphalt to maintain performance for a longer time.

[0023] (2) The chemically modified fiber prepared by the present invention effectively improves the reactivity of basalt fiber, enhances its reactivity and dispersion ability on the contact surface with magnesium phosphate cement, and greatly improves the mechanical properties of the repair material of the present invention. This is because: the present invention uses the active groups in the modifier to react with the surface of basalt, and the amino groups (-NH2) in the 3-aminopropyltriethoxysilane and aminophenylsilane react with the hydroxyl-OH or silicon-oxygen bonds on the surface of the basalt fiber to form a stable chemical connection. This reaction can enhance the adhesion of the amino group to the basalt fiber and help improve its interfacial compatibility with emulsified asphalt. The fluorine element contained in the trichlorofluorosilane can form a fluoride layer on the surface of the basalt fiber, enhance its hydrophobicity, and improve its bonding performance with asphalt. The styrene can chemically bond with the fiber surface through free radical polymerization to form a polystyrene layer, thereby improving the mechanical properties of the basalt fiber. The acrylic acid can form a covalent bond with the hydroxyl group on the surface of the basalt fiber through an esterification reaction, thereby enhancing the bonding between the fiber and organic matter such as asphalt.

[0024] (3) The interface enhancer of the present invention effectively eliminates the adverse effects of the interface transition zone between magnesium phosphate cement and emulsified asphalt in the repair material. This is because: magnesium phosphate cement releases a large amount of heat during the hydration process. The present invention uses the polyamide in the interface enhancer to provide extremely strong thermal stability and good bonding properties, which can be used to improve the adhesion of the interface enhancer, so that the interface transition zone between the repair material and the interface to be repaired (such as the road surface, airport runway, etc.) forms a cross-linked network, thereby improving the interface bonding strength. In addition, the phthalic anhydride and N,N-dimethylaniline can also chemically modify the epoxy resin. The phthalic anhydride reacts with the epoxy resin to form a cross-linked structure, thereby enhancing the strength and weather resistance of the interface enhancer, improving the stability of the interface bonding, and enhancing the interface corrosion resistance. The N,N-dimethylaniline can accelerate the curing process of the epoxy resin through a catalytic reaction, thereby improving the hardness and bonding strength of the interface enhancer. In addition, the N,N-dimethylaniline can also improve the rheological properties of the interface enhancer, making it easier to operate in practical applications. The rubber powder forms an elastic structure, which helps to improve the impact resistance of the repair material of the present invention, enhance the shock resistance and crack resistance, and thus helps to avoid the repair material from breaking or falling off under high stress conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a sample picture of the interface enhanced emulsified asphalt composite magnesium phosphate cement repair material prepared in the following Example 1.

[0026] Figure 2 The following is a graph showing the flexural strength test of Example 1.

[0027] Figure 3 The following is a compressive strength test diagram of Example 1.

[0028] Figure 4 This is a test diagram of the oblique shear bond strength of the following Example 1. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.

[0031] Example 1 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 5 mm long basalt fiber and 3% by mass sodium hydroxide solution were mixed at a ratio of 1 g: 25 ml and allowed to stand for 4 hours, then the fiber was filtered out, washed with clean water to remove the residual alkali solution, placed in trichlorofluorosilane, and heated to 60°C for 4 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 80°C for 20 hours to obtain the chemically modified fiber for later use.

[0032] (2) Mix epoxy resin, polycaprolactam, phthalic anhydride, butyl rubber powder and N,N-dimethylaniline in a mass ratio of 11:0.4:0.15:0.6:0.13 and stir evenly to obtain an interface enhancer for later use.

[0033] (3) Take the following raw materials in the following proportions: 480 parts by weight of magnesium phosphate cement-based material, 100 parts by weight of emulsified asphalt with a solid content of 50%, 7 parts by weight of toughening organic component (200-mesh waste tire powder), 12.5 parts by weight of optimizer (hexadecyl dimethyl benzyl ammonium chloride), 15 parts by weight of the interface enhancer prepared in this example, 6 parts by weight of the chemically modified fiber prepared in this example, and 95 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 240 parts by weight of magnesium oxide powder, 110 parts by weight of potassium dihydrogen phosphate, and 20 parts by weight of borax.

[0034] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material, such as Figure 1 shown.

[0035] Performance test: (1) According to GB / T 1346-2011 "Cement strength test method (method)", the 7d flexural strength of the magnesium phosphate cement repair material prepared in this embodiment was tested (such as Figure 2 As shown), 7d compressive strength (as shown Figure 3(2) A cement mortar specimen with a bottom side length of 40 mm and a height of 80 mm was used as a substrate, which was cut (with a cutting angle of 30°), and then the cross section was bonded with the magnesium phosphate cement repair material prepared in this embodiment. After hardening for 72 hours, an oblique shear bond strength test was performed (as shown in FIG. Figure 4 The test results of the above indicators are shown in the following table: .

[0036] Example 2 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 10 mm long basalt fiber and 2% by mass sodium hydroxide solution were mixed at a ratio of 1 g:40 ml and allowed to stand for 5 hours, then the fiber was filtered out, washed with clean water to remove the residual alkali solution, placed in 3-aminopropyltriethoxysilane, and heated to 50°C for 6 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 70°C for 24 hours to obtain the chemically modified fiber for later use.

[0037] (2) Mix epoxy resin, polyhexamethylene adipamide, phthalic anhydride, butyl rubber powder and N,N-dimethylaniline in a mass ratio of 9:0.3:0.1:0.6:0.15 and stir evenly to obtain an interface enhancer for later use.

[0038] (3) Take the following raw materials in the following proportions: 520 parts by weight of magnesium phosphate cement-based material, 70 parts by weight of emulsified asphalt with a solid content of 60%, 5 parts by weight of toughening organic component (SBS powder with a fineness of 300 mesh), 11 parts by weight of optimizer (sulfoaniline diethylenetriamine), 10 parts by weight of the interface enhancer prepared in this example, 4 parts by weight of the chemically modified fiber prepared in this example, and 90 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 180 parts by weight of magnesium oxide powder, 100 parts by weight of ammonium dihydrogen phosphate, and 15 parts by weight of borax.

[0039] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0040] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0041] Example 3 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 20 mm long basalt fiber and 4% sodium hydroxide solution by mass fraction were mixed at a ratio of 1 g:30 ml and allowed to stand for 3.5 hours, then the fiber was filtered out, washed with clean water to remove residual alkali solution, placed in styrene, and heated to 80°C for 2 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 60°C for 24 hours to obtain chemically modified fiber for later use.

[0042] (2) Mix epoxy resin, polyhexamethylene adipamide, phthalic anhydride, butyl rubber powder and N,N-dimethylaniline in a mass ratio of 15:0.5:0.2:1.0:0.18 and stir evenly to obtain an interface enhancer for later use.

[0043] (3) Take the following raw materials in the following proportions: 400 parts by weight of magnesium phosphate cement-based material, 50 parts by weight of emulsified asphalt with a solid content of 60%, 7.5 parts by weight of toughening organic component (polyethylene rubber powder with a fineness of 250 mesh), 10 parts by weight of optimizer (2-ethylhexyl terephthalate), 8 parts by weight of the interface enhancer prepared in this example, 6 parts by weight of the chemically modified fiber prepared in this example, and 80 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 300 parts by weight of magnesium oxide powder, 150 parts by weight of potassium dihydrogen phosphate, and 30 parts by weight of triethanolamine.

[0044] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0045] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0046] Example 4 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 30 mm long basalt fiber and 5% by mass potassium hydroxide solution were mixed at a ratio of 1 g: 20 ml and allowed to stand for 6 hours, then the fiber was filtered out, washed with clean water to remove residual alkali solution, placed in styrene, and heated to 70°C for 4 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 70°C for 21 hours to obtain the chemically modified fiber for later use.

[0047] (2) Mix epoxy resin, polycaprolactam, phthalic anhydride, butyl rubber powder and N,N-dimethylaniline in a mass ratio of 8:0.35:0.15:0.5:0.1 and stir evenly to obtain an interface enhancer for later use.

[0048] (3) Take the following raw materials in the following proportions: 510 parts by weight of magnesium phosphate cement-based material, 120 parts by weight of emulsified asphalt with a solid content of 55%, 10 parts by weight of toughening organic component (polypropylene fiber powder with a fineness of 400 mesh), 13 parts by weight of optimizer (hexadecyl dimethyl benzyl ammonium chloride), 16 parts by weight of the interface enhancer prepared in this example, 8 parts by weight of the chemically modified fiber prepared in this example, and 95 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 150 parts by weight of magnesium oxide powder, 70 parts by weight of potassium dihydrogen phosphate, and 10 parts by weight of boric acid.

[0049] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0050] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0051] Example 5 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 10 mm long basalt fiber and 1% potassium hydroxide solution by mass fraction were mixed at a ratio of 1 g:35 ml and allowed to stand for 2 hours, then the fiber was filtered out, washed with clean water to remove residual alkali solution, placed in acrylic acid, and heated to 80°C for 3 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 60°C for 24 hours to obtain chemically modified fiber for later use.

[0052] (2) Mix epoxy resin, polycaprolactam, phthalic anhydride, nitrile rubber powder and N,N-dimethylaniline in a mass ratio of 14:0.5:0.18:0.9:0.2 and stir evenly to obtain an interface enhancer for later use.

[0053] (3) Take the following raw materials in the following proportions: 600 parts by weight of magnesium phosphate cement-based material, 150 parts by weight of emulsified asphalt with a solid content of 50%, 8 parts by weight of toughening organic component (polyurethane powder with a fineness of 200 mesh), 15 parts by weight of optimizer (thiobenzenesulfonic acid), 20 parts by weight of the interface enhancer prepared in this example, 10 parts by weight of the chemically modified fiber prepared in this example, and 100 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 200 parts by weight of magnesium oxide powder, 80 parts by weight of sodium dihydrogen phosphate, and 15 parts by weight of borax.

[0054] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0055] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0056] Example 6 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Preparation of chemically modified fiber: 20 mm long basalt fiber and 3% potassium hydroxide solution by mass fraction were mixed at a ratio of 1 g:40 ml and allowed to stand for 4 hours, then the fiber was filtered out, washed with clean water to remove residual alkali solution, placed in aminophenylsilane, and heated to 80°C for 5 hours. After completion, the fiber was filtered out, washed with clean water, and then dried at 60°C for 24 hours to obtain chemically modified fiber for later use.

[0057] (2) Mix epoxy resin, polyterephthalamide, phthalic anhydride, ethylene propylene rubber powder and N,N-dimethylaniline in a mass ratio of 10:0.4:0.3:0.7:0.15 and stir evenly to obtain an interface enhancer for later use.

[0058] (3) Take the following raw materials in the following proportions: 450 parts by weight of magnesium phosphate cement-based material, 80 parts by weight of emulsified asphalt with a solid content of 60%, 7.2 parts by weight of toughening organic component (ethylene-vinyl acetate copolymer powder with a fineness of 300 mesh), 10 parts by weight of optimizer (di-2-ethylhexyl phthalate), 13 parts by weight of the interface enhancer prepared in this example, 5 parts by weight of the chemically modified fiber prepared in this example, and 85 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 300 parts by weight of magnesium oxide powder, 100 parts by weight of potassium dihydrogen phosphate, and 20 parts by weight of borax.

[0059] (4) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0060] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0061] Example 7 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 550 parts by weight of magnesium phosphate cement-based material, 110 parts by weight of emulsified asphalt with a solid content of 60%, 8 parts by weight of toughening organic component (polyethylene rubber powder with a fineness of 200 mesh), 13 parts by weight of optimizer (cyclohexyl phenyl ester), 15 parts by weight of the interface enhancer prepared in Example 1, 7 parts by weight of the chemically modified fiber prepared in Example 1, 96 parts by weight of mixing water, 5 parts by weight of polycarboxylate water reducer, and 2 parts by weight of organosilicon defoamer. The magnesium phosphate cement-based material is prepared by mixing 160 parts by weight of magnesium oxide powder, 80 parts by weight of potassium dihydrogen phosphate, and 14 parts by weight of borax.

[0062] (2) The chemically modified fiber, toughening organic component, optimizer, water reducer, defoamer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0063] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0064] Example 8 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 420 parts by weight of magnesium phosphate cement-based material, 60 parts by weight of emulsified asphalt with a solid content of 55%, 9 parts by weight of toughening organic component (polyethylene rubber powder with a fineness of 400 mesh), 10 parts by weight of optimizer (octaalkyl sulfobetaine), 10 parts by weight of the interface enhancer prepared in Example 2, 5 parts by weight of the chemically modified fiber prepared in Example 2, 82 parts by weight of mixing water, 3 parts by weight of sodium lignin sulfonate water reducer, and 1 part by weight of fatty acid defoamer. The magnesium phosphate cement-based material is prepared by mixing 200 parts by weight of magnesium oxide powder, 80 parts by weight of sodium dihydrogen phosphate, and 15 parts by weight of borax.

[0065] (2) The chemically modified fiber, toughening organic component, optimizer, water reducer, defoamer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0066] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0067] Example 9 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 500 parts by weight of magnesium phosphate cement-based material, 100 parts by weight of emulsified asphalt with a solid content of 55%, 8 parts by weight of toughening organic component (hydroxymethyl cellulose powder with a fineness of 200 mesh), 13 parts by weight of optimizer (sodium p-toluenesulfonate), 16 parts by weight of the interface enhancer prepared in Example 4, 8 parts by weight of the chemically modified fiber prepared in Example 4, 90 parts by weight of mixing water, 7 parts by weight of naphthalene-based water reducer, and 4 parts by weight of polyether defoamer. The magnesium phosphate cement-based material is prepared by mixing 300 parts by weight of magnesium oxide powder, 100 parts by weight of potassium dihydrogen phosphate, and 20 parts by weight of borax.

[0068] (2) The chemically modified fiber, toughening organic component, optimizer, water reducer, defoamer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0069] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0070] Example 10 A method for preparing an emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 480 parts by weight of magnesium phosphate cement-based material, 100 parts by weight of emulsified asphalt with a solid content of 50%, 7 parts by weight of toughening organic component (200-mesh waste tire powder), 15 parts by weight of the interface enhancer prepared in Example 1, 6 parts by weight of the chemically modified fiber prepared in Example 1, and 95 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 240 parts by weight of magnesium oxide powder, 110 parts by weight of potassium dihydrogen phosphate, and 20 parts by weight of borax.

[0071] (2) The chemically modified fiber, toughening organic component and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0072] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0073] Embodiment 11 A method for preparing an emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 520 parts by weight of magnesium phosphate cement-based material, 70 parts by weight of emulsified asphalt with a solid content of 60%, 5 parts by weight of toughening organic component (SBS powder with a fineness of 300 mesh), 11 parts by weight of optimizer (sulfoaniline diethylenetriamine), 4 parts by weight of the chemically modified fiber prepared in this example, and 90 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 180 parts by weight of magnesium oxide powder, 100 parts by weight of ammonium dihydrogen phosphate, and 15 parts by weight of borax.

[0074] (2) The chemically modified fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0075] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0076] Example 12 A method for preparing an interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material comprises the following steps: (1) Take the following raw materials in the following proportions: 400 parts by weight of magnesium phosphate cement-based material, 50 parts by weight of emulsified asphalt with a solid content of 60%, 7.5 parts by weight of toughening organic component (polyethylene rubber powder with a fineness of 250 mesh), 10 parts by weight of optimizer (2-ethylhexyl terephthalate), 8 parts by weight of the interface enhancer prepared in Example 3, 6 parts by weight of basalt fiber with a length of 20 mm, and 80 parts by weight of mixing water. The magnesium phosphate cement-based material is prepared by mixing 300 parts by weight of magnesium oxide powder, 150 parts by weight of potassium dihydrogen phosphate, and 30 parts by weight of triethanolamine.

[0077] (2) The basalt fiber, toughening organic component, optimizer and mixing water are mixed and stirred evenly, and then the emulsified asphalt is added and stirred for 1 minute, and then the magnesium phosphate cement-based material is added and stirred for 4 minutes, and finally the interface enhancer is added and stirred evenly to obtain an emulsified asphalt composite magnesium phosphate cement repair material.

[0078] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0079] Embodiment 13 A method for preparing an emulsified asphalt composite magnesium phosphate cement repair material is the same as the above-mentioned Example 4, except that the chemically modified fiber of this example is prepared by the following method: basalt fiber with a length of 30 mm and a potassium hydroxide solution with a mass fraction of 5% are mixed in a ratio of 1 g:20 ml and allowed to stand for 6 hours, and then the fiber is filtered out, washed with clean water to remove residual alkali solution, and dried at 70°C for 21 hours to obtain the chemically modified fiber.

[0080] Performance test: The same method as in Example 1 was used to test the 7d flexural strength, 7d compressive strength and oblique shear bond strength of the magnesium phosphate cement repair material prepared in this example. The test results are shown in the following table: .

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still repair the technical solutions recorded in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any repair, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material, characterized in that: The invention comprises the following components in parts by weight: 400-600 parts of magnesium phosphate cement-based materials, 50-150 parts of emulsified asphalt, 5-10 parts of toughening organic components, 10-15 parts of optimizers, 8-20 parts of interface enhancers, 4-10 parts of chemically modified fibers and 80-100 parts of mixing water.

2. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 1, characterized in that: The magnesium phosphate cement-based material comprises: 150-300 parts by weight of magnesium oxide powder, 70-150 parts by weight of phosphate, and 10-30 parts by weight of retarder; or, the solid content of the emulsified asphalt is 50-60%.

3. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 1, characterized in that: The toughening organic component includes: at least one of waste tire powder, polyethylene rubber powder, polyurethane rubber powder, styrene-butadiene-styrene rubber powder, polypropylene fiber powder, cellulose ether powder, and ethylene-vinyl acetate copolymer rubber powder; or the fineness of the toughening organic component is 200-400 meshes.

4. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 1, characterized in that: The optimizer comprises: at least one of thiobenzenesulfonic acid, sulfoaniline diethylenetriamine, cyclohexylphenyl ester, 2-ethylhexyl terephthalate, diisooctyl phthalate, octaalkyl sulfobetaine, sodium p-toluenesulfonate, and hexadecyl dimethylbenzyl ammonium chloride.

5. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 1, characterized in that: The interface enhancer is formed by mixing epoxy resin, polyamide, phthalic anhydride, rubber powder and N,N-dimethylaniline in a mass ratio of 8-15:0.3-0.5:0.1-0.3:0.5-1:0.1-0.2; the polyamide includes at least one of polyhexamethylene adipamide, polyterephthalamide and polycaprolactam.

6. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 1, characterized in that: The preparation method of the chemically modified fiber comprises: placing basalt fiber in an alkaline solution and letting it stand; after completion, separating the basalt fiber, washing it and placing it in a modifier for heating and heat preservation treatment; after completion, washing the fiber and drying it to obtain the chemically modified fiber; the modifier comprises at least one of trichlorofluorosilane, 3-aminopropyltriethoxysilane, aminophenylsilane, styrene and acrylic acid.

7. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 6, characterized in that: The ratio of basalt fiber to alkali solution is 1g: 20-40ml; Alternatively, the mass fraction of the alkali solution is 1-5%; Alternatively, the alkali solution includes any one of sodium hydroxide solution, potassium hydroxide solution, and ammonia water; Alternatively, the length of the basalt fiber is 5 to 30 mm; Alternatively, the standing time is 2 to 6 hours.

8. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to claim 6, characterized in that: The heating temperature is 50-80° C., and the heat preservation time is 2-6 hours; or, the drying temperature is 60-80° C., and the drying time is 20-24 hours.

9. The interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to any one of claims 1 to 8, characterized in that: The repair material also includes 3 to 7 parts by weight of a water reducing agent and 1 to 4 parts by weight of a defoaming agent.

10. Use of the interface-enhanced emulsified asphalt composite magnesium phosphate cement repair material according to any one of claims 1 to 9 in construction engineering, road engineering, bridge engineering, water conservancy and hydropower engineering or marine engineering.

Citation Information

Patent Citations

  • Asphalt modified by epoxy resin and rubber powder

    CN101085871A

  • Road asphalt modifier

    CN102964854A

  • Basalt fiber reinforced cement based material and preparation method therefor

    CN105541209A

  • Modified basalt fiber reinforced basic magnesium sulfate cement and preparation method thereof

    CN115572145A

  • Saline-alkali-tolerant modified emulsified asphalt composite phosphorus-magnesium-based cement material and preparation method thereof

    CN118324449A

Cited By

  • Preparation process of marine concrete structure surface anti-erosion cement-based material

    CN122254858A